Teacher expectations concerning students with immigrant backgrounds or special educational needs. Issue 3 (3rd April 2018) - Pit-ten Cate, Ineke M.; Glock, Sabine
ABSTRACT: Male students with immigrant backgrounds are disproportionally referred for special educational support outside regular classrooms or schools, which may reflect differential teachers' expectations concerning the academic achievement of students based on sociodemographic characteristics. Although research has indicated differential teachers' expectations for students based on immigrant background or special educational needs (SEN), less is known about a possible double vulnerability associated with combined stereotypes. Therefore, in the current study, both SEN and immigrant background were systematically varied and teachers were asked to rate the students' academic achievement. Results showed that teachers' expectations of students with SEN and immigrant background were lower than for students without immigrant background, especially in regards to language proficiency. These results may help to explain the overrepresentation of students with immigrant background in special education programmes. The educational and theoretical implications of these findings are discussed.